Early Speech Acts in Child Language - Vintoni, Aridem (Institut Agama Islam Negeri (IAIN) Curup, 2017)
Abstract Each utterance is designed to serve a specific function. It may be meant to inform the listeners, warn them, order them to do something, question them about the fact, or thank them for a gift or act of kindness. All of these speech acts are called as the communicative functions of language or the functions of speech acts. Therefore, in communicating, people do not just â€œsay thingsâ€, but also perform certain â€œactionsâ€.In the process of language development in children, the development of the language functions or speech acts (i.e. illocutionary speech acts) occur simultaneously with the development of linguistics aspects of language (phonemes or sounds, morpheme, words, and sentences) in each stages of language development. The development began early from infants start to babble, produce single-word utterances, until they produced more complex sentences. However, how is the process of the evolution at the early stage of child language development? How do children use their language at the early stage of the development?In this short paper, the writer describes thesome forms of speech acts produced by children.